Employment Protection Through the Perspective of Fulfilling Citizens’ Rights in Indonesia - SH MH, Nuridin; SH MH, Sanusi; SH MH, Tiyas Vika Widyastuti (International Journal of Engineering and Technology, 2018)
Outsourcing system is a prevalent form of employee recruitment in Indonesia. The Employment Relationship of Outsourcing System under the provisions of Law Number 23 of 2003 concerning Employment so far has not been able to deliver welfare for workers/ labors, in return for their contribution to the companiesâ€™ productivity improvement. Labors do not obtain their rights which have been warranted in the Law. Additionally, outsourcing system has created uncertainty in employment relationship. This research uses the paradigm of constructivism and selected macro and micro theories to analyze the problems surrounding employment protection. We also employ qualitative method with a socio-legal approach. Our contention is that a change is critically needed to be made to the regulations of law which govern employment relationship or partial transfer of job to a third party. The change should reflect what the workers/ labors wish. It should also bear values such as justice and welfare for workers/ labors. This is all meant to achieve a harmonious and just employment relationship based on Pancasila (The Five Pillars of Indonesian State Ideology) and the Indonesian 1945 Constitutionn. Â Â